Comprehensive Assessment and Trading Mechanism of Carbon Sink in China’s Marine Aquaculture - Xuan Yu; Haonan Guo; Qi Chen (Biology)
This study develops species-specific assessment models for carbon sink in marine aquaculture (CSMA) using provincial data from China’s coastal regions (2004–2023). Key findings are as follows: (1) Cumulative CSMA reached 46.3618 million tonnes, exhibiting three growth phases—initial fluctuations (2004–2008), rapid growth (2008–2015), and optimization and maturation (2015–2023). (2) Species contributions were heterogeneous: shellfish dominated at 45%, followed by shrimp (24%), fish (15%), crab (11%), and algae (5%). (3) Spatially, Guangdong, Fujian, and Shandong consistently lead in CSMA; Guangxi, Liaoning, and Zhejiang form a second tier, whereas Hebei, Hainan, and Jiangsu remain at the lower end. (4) Province-specific dominance patterns were observed: shellfish-dominant pattern in Shandong, Fujian, and Liaoning; shrimp-dominant pattern in Hebei and Hainan; shellfish-and-shrimp dual-cores in Guangdong and Guangxi; and a multifaceted profile in Jiangsu and Zhejiang. To facilitate the realization of CSMA’s value, we propose a dedicated trading mechanism. Based on the derivations from the effect analysis model and the illustrative case studies, we explore the potential economic and ecological benefits of CSMA trading.